2011
DOI: 10.1021/ja211042r
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazinones Are Suicide Inhibitors of Mycobacterial Decaprenylphosphoryl-β-d-ribofuranose 2′-Oxidase DprE1

Abstract: Benzothiazinones (BTZs) are antituberculosis drug candidates with nanomolar bactericidal activity against tubercle bacilli. Here we demonstrate that BTZs are suicide substrates of the FAD-dependent decaprenylphosphoryl-β-D-ribofuranose 2′-oxidase DprE1, an enzyme involved in cell-wall biogenesis. BTZs are reduced by DprE1 to an electrophile, which then reacts in a nearquantitative manner with an active-site cysteine of DprE1, thus providing a rationale for the extraordinary potency of BTZs. Mutant DprE1 enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
163
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 166 publications
(172 citation statements)
references
References 14 publications
4
163
0
Order By: Relevance
“…8,9 The detailed mechanistic and proteomics studies carried out by Makarov and Trefzer et al 6,8,9 have shown that the cysteine at the active site is essential for the anti-TB activity of 1 and 2 and its mutation to any other amino acid resulted in the dramatic loss of activity. Our efforts related to the mechanistic understanding of the reductive activation of 1 suggest that 1 and other related nitroaromatic anti-TB agents may undergo chemical activation of the constituent nitro group to the nitroso intermediate by a cine addition reaction ( Figure 2B).…”
Section: T Uberculosis (Tb) Is a Disease Mainly Caused Bymentioning
confidence: 99%
“…8,9 The detailed mechanistic and proteomics studies carried out by Makarov and Trefzer et al 6,8,9 have shown that the cysteine at the active site is essential for the anti-TB activity of 1 and 2 and its mutation to any other amino acid resulted in the dramatic loss of activity. Our efforts related to the mechanistic understanding of the reductive activation of 1 suggest that 1 and other related nitroaromatic anti-TB agents may undergo chemical activation of the constituent nitro group to the nitroso intermediate by a cine addition reaction ( Figure 2B).…”
Section: T Uberculosis (Tb) Is a Disease Mainly Caused Bymentioning
confidence: 99%
“…The nitro group of these compounds is reduced specifically by DprE1 to a nitroso group, which then reacts with a key active site cysteine residue (Cys387 in M. tuberculosis) to form an irreversible covalent adduct. The nitro group of the BTZs is essential for this mechanism of inhibition, as earlier structure-activity relationship (SAR) studies demonstrated that its replacement by groups such as H, Br, CN, CF 3 , NH 2 , N,Ndiacetyl, NCHN-dimethyl, NCH-phenyl, furyl, COOR, and COH led to MIC increases of Ͼ500-fold with respect to BTZ043 and greatly reduced bactericidal activity (1,11). These substitutions were introduced because of concerns about potential mutagenicity associated with the nitro group, although the concerns have proved groundless.…”
Section: T He Discovery Of the 8-nitro-benzothiazinone (Btz) Lead Commentioning
confidence: 99%
“…BTZ behaves as a suicide substrate for the reduced form of DprE1 by undergoing nitroreduction to form a nitroso derivative, which specifically forms a covalent adduct with C387 in the DprE1 active site (7)(8)(9)(10). The C387 residue of DprE1 is highly conserved in orthologous enzymes in actinobacteria, except in Mycobacterium avium and M. aurum, where cysteine is replaced by alanine and serine, respectively.…”
mentioning
confidence: 99%